Molecular Techniques For Medical Microbiology Laboratories: Futuristic Approach In Diagnostics Of Infectious Diseases - ANJUM GAHLAUT; ASHISH GOTHWAL; ANIL K CHHILLAR; VIKAS HOODA (International Journal of Pharma and Bio Sciences, 2012)
Diagnostic methods for infectious diseases have stagnated in the last 20–30 years. Conventional diagnostic approaches are not able to fulfill all the desires needed for the effective diagnosis of microbial diseases. Few major advances in clinical diagnostic tools have been achieved after the introduction of PCR, although new techniques are under investigation. Many tools that are used in the “modern” microbiology laboratory are based on very old and labor-intensive technologies. The need to develop new diagnostic tools include more rapid tests without sacrificing sensitivity, reliable, accurate, value-added tests, and point-of-care test. Research has been focused toward development of new alternative methods to improve the diagnosis of microbial diseases. These include molecular-based approaches. This review summarizes some of the new molecular approaches in microbial disease diagnosis.